EDUCATION FOR PUBLIC ACCOUNTING. - Vance, Lawrence L. (The Accounting Review, 1956)
Abstract The training of recruits for a profession is a topic of perennial interest to practioners of the art as well as to educators. This can be seen in a variety of circumstances, in the formal qualifications required of candidates for admission, in the many discussions of the problem which stud the literature, in the continuous existence of committees on education in professional organizations, in the responses of practitioners to invitations to appear before students, and in the occasional appointment of commissions to review the educational process. This concern is vital to the improvement of the profession and perhaps to its continued existence. For instance, the College of Accountants in Venice, which was founded in 1581 and later achieved a status similar to that of state boards of accountancy, admitted members to the college or society by requiring, first, a certificate of fitness from a magistrate, second, an apprenticeship of six years, third, a certificate from a magistrate on the legal attainments of the candidate, fourth, a declaration by the accountant under whom he had served as to his ability, fifth, an examination before a board of examiners, and sixth, another examination before the governing body.